2006
DOI: 10.1007/s00276-006-0075-2
|View full text |Cite
|
Sign up to set email alerts
|

A rich lymphatic network exists in the inferior surface of the vocal cord

Abstract: Conservation laryngeal surgery is an increasingly available alternative for the treatment of laryngeal cancer. Understanding anatomy of laryngeal lymph drainage is essential for clinicians to diagnose, grade and surgically manage the laryngeal cancer. Although the lymphatic drainage of the larynx has been extensively studied, few studies revealed the relationship of the lymphatic drainage between various parts of the larynx. The distribution of lymphatic vessels in the inferior surface of the vocal cord also r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Therefore this study clearly demonstrates the presence of lymphatics in the LP in the elderly population and confirms evidence provided by others that the vocal folds do have lymphatic drainage. Liu et al (2006) used fetal VF tissue to show that there is a rich supply of lymphatics on the inferior surface of the VF while comparatively less lymphatic vessels drain the superior VF surface. These lymphatics are described as running parallel to the free margin of the VF, suggesting that they must exit the VF at the anterior and posterior attachments of the VF like the vocal blood vessels (Liu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore this study clearly demonstrates the presence of lymphatics in the LP in the elderly population and confirms evidence provided by others that the vocal folds do have lymphatic drainage. Liu et al (2006) used fetal VF tissue to show that there is a rich supply of lymphatics on the inferior surface of the VF while comparatively less lymphatic vessels drain the superior VF surface. These lymphatics are described as running parallel to the free margin of the VF, suggesting that they must exit the VF at the anterior and posterior attachments of the VF like the vocal blood vessels (Liu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (2006) used fetal VF tissue to show that there is a rich supply of lymphatics on the inferior surface of the VF while comparatively less lymphatic vessels drain the superior VF surface. These lymphatics are described as running parallel to the free margin of the VF, suggesting that they must exit the VF at the anterior and posterior attachments of the VF like the vocal blood vessels (Liu et al, 2006). In this study the lymphatics that were observed on the superior VF surface were sectioned longitudinally, indicating that they were running perpendicular to the VF margin.…”
Section: Discussionmentioning
confidence: 99%
“…The orientation of the lymphatic vessels was quite similar to that of the blood vessels: In humans, the lymphatics of the free edge of the vocal fold run in the direction of the fold's long axis, while the lymphatics in the ventricle and in the area of the subglottis run perpendicular to the vocal fold's long axis [18,34,44,45]. In the porcine glottis, the situation is basically the same, but two peculiar findings made the system more special: many lymphatic vessels on the CraF's caudal side, and in the ventricular fundus, and on the CauF's cranial side ran perpendicular to the folds' long axes.…”
Section: Discussionmentioning
confidence: 83%
“…In the porcine glottis, the situation is basically the same, but two peculiar findings made the system more special: many lymphatic vessels on the CraF's caudal side, and in the ventricular fundus, and on the CauF's cranial side ran perpendicular to the folds' long axes. The direction of lymph drainage -towards the arytenoid region and towards the ventricular fundus in the CraF and CauF -appears to be analogous to that in the human vocal fold [18,34,44,45].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation